PENGARUH QIRAAH SHADHDHAH DALAM PENAFSIRAN AYAT AL-QUR’AN - Umar Zakka; M. Fadli Rosyid; M Thohir (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2022)
Qiraah shaddhhah are readings that are not in accordance with the readings that have been agreed upon by the Qira'at scholars, because they do not meet one of the conditions for the acceptance of the reading of the Qur'an. Abd al-Aliy al-Mas'ul divides qiraah shadhdhah into four, namely sawtiyyan, sarfiyyan, nahwiyyan and dalaliyyan. While Ahmad al-Bayliy divides it into three, namely al-mashrurah, al-ahad and al-mudraj. The majority of scholars agree on the permissibility of recording, studying and teaching it, as well as using it as a basis or argument for language studies, and also using it as a tool to understand the meaning of qiraah mutawatirah, if the sanad is valid. However, the scholars have different opinions regarding the use of qiraah shadhdhah in legal istinbat, which allow the Hanafi, Hanabilah and some scholars from the Shafi'i and Maliki schools, while those who prohibit are the majority of the Maliki, Shafi'i and Ibn Hazm al-Islamic scholars. -Zahiriy. The results of this study are, first: qiraah shadhdhah is qiraah that does not meet one of the requirements for receiving the Qur'an, or in simple terms it can be said that qiraah shadhdhah is qiraah outside of qiraah 'ashr (ten), but qiraah shadhdhah can still be used as reinforcing the interpretation of an interpretation resulting from qira'ah mutawatir. Second: the effect of qiraah shadhdhah on the interpretation of the Qur'an from the perspective of mapping Abd al-Aliy al-Mas'ul, only on the type of qiraah shadhdhah dalaliyyan, while the types of qiraah shadhdhah sawtiyyan, sarfiyyan and nahwiyyan, have no effect on the interpretation of the Qur'an . Meanwhile, the influence of qira'ah shadhdhah on the interpretation of the Qur'an from the perspective of Ahmad al-Bayliy's mapping is found in the types of al-qira'ah al-ahad and al-qira'ah al-mudrajah, while al-qira'ah al-shadhdhah al-mashhurah does not affect the interpretation of the Qur'an